Anti-shrinkage-cracking high-fluidity early-strength support grouting material and preparation method thereof

By combining quaternary cement clinker and graphene oxide-modified microspheres, the shrinkage cracking and strength reduction problems of early-strength bearing grouting materials are solved, the hydration reaction path is optimized, the fluidity and stability of early-strength bearing grouting materials are improved, and the quality of the project is ensured.

CN121044849APending Publication Date: 2025-12-02BBMG MORTAR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511296833.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-11
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Traditional early-strength bearing grouting materials are prone to shrinkage cracking and strength reduction during construction. The concentrated heat release during early hydration affects the safety of the material, and graphene oxide has poor dispersion in the cement matrix, making it difficult to play a reinforcing role.

Method used

A combination of quaternary cement clinker, graphene oxide modified microspheres, early strength agent, water-reducing agent, retarder and expansion agent is used. Through modification process, graphene oxide is uniformly loaded on the surface of microspheres, optimizing the hydration reaction path, improving dispersibility and fluidity, alleviating early hydration heat accumulation, and enhancing material stability.

Benefits of technology

It achieves early strength enhancement of high-flowability, early-strength bearing grout, prevents shrinkage cracking, extends construction operation time, ensures project quality stability, and possesses excellent construction performance and subsequent strength growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005591805450000151
    Figure BDA0005591805450000151
  • Figure BDA0005591805450000161
    Figure BDA0005591805450000161
Patent Text Reader

Abstract

The invention provides a shrinkage-cracking-resistant high-fluidity early-strength support grouting material and a preparation method thereof. The graphene oxide modified micro-bead cement is prepared from the following components in parts by weight: 40 to 50 parts of quaternary cement clinker, 45 to 55 parts of quartz sand, 3 to 5 parts of graphene oxide modified micro-beads, 0.01 to 0.03 part of early strength agent, 0.2 to 0.4 part of water reducing agent, 0.3 to 0.5 part of retarder, 0.03 to 0.05 part of expanding agent and 0.05 to 0.08 part of defoaming agent. The graphene oxide modified microspheres are prepared by the following steps: uniformly mixing modified fly ash microspheres and a graphene oxide dispersion liquid according to a ratio of 1g: (20-30) ml, adding N-hydroxysuccinimide with the same mass as graphene oxide, carrying out a water bath reaction, immersing a product into a polyethylene glycol solution, and carrying out a water bath reaction again. The graphene oxide modified microbeads are prepared by a specific method, and the problems of shrinkage cracking and strength shrinkage of a traditional early-strength grouting material in the later stage are effectively solved through the synergistic effect of the modified microbeads, the quaternary cement clinker and the specific graded quartz sand; the adverse effect of an early hydration heat release concentration phenomenon on the safety of the material is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bearing grouting technology, specifically relating to a high-flowability, early-strength bearing grouting material with shrinkage crack resistance and its preparation method. Background Technology

[0002] Bridge bearing grout is widely used in the installation and maintenance of bridge bearings, especially suitable for different types of engineering needs such as precast beams, cast-in-place beams, and extra-large bridges. As a key structural material, its performance directly affects the load-bearing efficiency and long-term durability of bridge structures. With the rapid development of transportation infrastructure construction, especially the large-scale expansion of highway and high-speed railway networks, traditional grouting materials can no longer meet the stringent requirements of modern engineering. Compared with ordinary grout, the core advantage of early-strength bearing grout lies in its ultra-high early strength (compressive strength of 20-30MPa at 2 hours and 40-60MPa at 24 hours), which can significantly shorten the construction cycle. It is especially suitable for scenarios requiring rapid traffic opening, such as bridge bearing installation and railway track anchoring. Its fluidity is better (initial fluidity ≥320mm, 30-minute fluidity ≥240-280mm), and it has self-leveling properties, filling gaps without vibration. Moreover, its micro-expansion performance (28-day expansion rate of 0.02-0.6%) can avoid shrinkage cracking and ensure tight bonding with the substrate. Ordinary grouting materials have low early strength (24-hour strength approximately ≥20MPa), poor fluidity, and require long-term curing after construction, making them unsuitable for emergency repairs or low-temperature environments.

[0003] Currently, early-strength bearing grouting materials are mainly based on sulfoaluminate cement (SAC) as the cementitious material system, typically accounting for 40-50%. This system mainly achieves early strength through the rapid crystallization of ettringite (AFt), with a compressive strength reaching 20 MPa in 2 hours. It also exhibits rapid hydration and good adaptability to low-temperature environments, making it widely used in engineering scenarios requiring rapid construction or low-temperature operations. However, this system often suffers from the following performance defects in practical applications: Firstly, the intense hydration reaction of sulfoaluminate cement makes setting time control difficult, easily leading to premature setting or excessively rapid setting, affecting construction operations; secondly, the heat released during hydration is too concentrated, easily creating significant temperature stress within the material. Furthermore, under low water-cement ratio formulations, the material also generates significant self-shrinkage stress, exacerbating the risks of mid-to-late-stage strength reduction and cracking. Meanwhile, although existing technologies have attempted to introduce graphene or fly ash microspheres to improve the performance of grouting materials, graphene tends to agglomerate in the cement matrix, making it difficult to exert a reinforcing effect; fly ash microspheres have a strong surface inertness and weak interfacial bonding with the cement matrix, resulting in limited modification effects.

[0004] To address the aforementioned issues, the development of an early-strength bearing grout that simultaneously achieves high mechanical strength, excellent flowability, and resistance to shrinkage cracking is of significant practical importance. Summary of the Invention

[0005] The purpose of this invention is to provide a high-flowability, early-strength bearing grout that is resistant to shrinkage and cracking. On the one hand, it effectively solves the problems of shrinkage cracking and strength reduction that occur in the later use of traditional early-strength bearing grouts. On the other hand, it alleviates the adverse effects of the concentrated heat release phenomenon in early hydration on the safety of the material. At the same time, it comprehensively improves the workability and performance stability of the product, providing a reliable guarantee for the safety and quality of the project.

[0006] To achieve the above objectives, the present invention provides a shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grout, comprising the following components by weight:

[0007] 40-50 parts of quaternary cement clinker, 45-55 parts of quartz sand, 3-5 parts of graphene oxide modified microspheres, 0.01-0.03 parts of early strength agent, 0.2-0.4 parts of water-reducing agent, 0.3-0.5 parts of retarder, 0.03-0.05 parts of expansion agent and 0.05-0.08 parts of defoamer.

[0008] In a preferred embodiment, the total weight of the quaternary cement clinker, quartz sand, and graphene oxide modified microspheres is 100 parts.

[0009] In a preferred embodiment, the mineral composition and mass percentage of the quaternary cement clinker are as follows: tricalcium silicate 25-40%, dicalcium silicate 15-25%, calcium sulfoaluminate 20-30%, tricalcium aluminate 5-20%, tetracalcium aluminoferrite 4-7%, calcium sulfosilicate 5-15%, free calcium oxide not more than 2%, and the mass sum of calcium sulfoaluminate and tricalcium aluminate not less than 35%.

[0010] In a preferred embodiment, the quartz sand is prepared by compounding quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh and 40-140 mesh in a mass ratio of 3:5:2.

[0011] In a preferred embodiment, the graphene oxide modified microspheres are prepared by a method comprising the following steps:

[0012] Preparation of modified fly ash microspheres: The pretreated fly ash microspheres were dispersed in anhydrous ethanol solution of γ-aminopropyltriethoxysilane and reacted in a water bath at 55-65℃ for 3-5 hours to obtain modified fly ash microspheres.

[0013] Preparation of graphene oxide dispersion: Graphene oxide was dispersed in ammonia water and ultrasonically treated to obtain graphene oxide dispersion.

[0014] Preparation of graphene oxide modified microspheres: The prepared modified fly ash microspheres and graphene oxide dispersion were mixed evenly at a mass-to-volume ratio of 1g:(20-30)ml. N-hydroxysuccinimide of the same mass as the graphene oxide dispersion was added. The mixture was stirred and reacted in a water bath at 55-65℃ for 3-5 hours. After filtration, the reaction product was collected and immersed in a polyethylene glycol (PEG) solution with a mass fraction of 8-12%. The mixture was then reacted in a water bath at 70-90℃ for 1-3 hours. The resulting product was dried to obtain graphene oxide modified microspheres.

[0015] Preferably, in the step of preparing modified fly ash microspheres, the pretreatment method of the fly ash microspheres specifically includes: mixing fly ash microspheres with a hydrochloric acid solution with a mass fraction of 2-10%, shaking at room temperature for 10-30 minutes, washing with water until neutral, and vacuum drying at 40-60℃ for 1-3 hours to remove surface impurities; wherein, the mass-to-volume ratio of fly ash microspheres to hydrochloric acid solution is 1 g:(20-30) ml.

[0016] Preferably, in the step of preparing modified fly ash microspheres, the mass-to-volume ratio of the pretreated fly ash microspheres and the γ-aminopropyltriethoxysilane anhydrous ethanol solution is 1 g:(10-20) ml.

[0017] Preferably, in the step of preparing modified fly ash microspheres, the mass fraction of the γ-aminopropyltriethoxysilane anhydrous ethanol solution is 1-3%; more preferably, the mass fraction of the γ-aminopropyltriethoxysilane anhydrous ethanol solution is 2%.

[0018] Preferably, in the step of preparing modified fly ash microspheres, the water bath reaction conditions include: reacting in a water bath at 55-65°C for 3-5 hours.

[0019] Preferably, in the step of preparing modified fly ash microspheres, after the water bath reaction is completed, the mixture is further washed 2-4 times with anhydrous ethanol.

[0020] Preferably, in the step of preparing the graphene oxide dispersion, the mass-to-volume ratio of the graphene oxide and ammonia is (0.2-0.8) mg / ml.

[0021] Preferably, in the step of preparing the graphene oxide dispersion, the pH of the ammonia water is 8-10; more preferably, the pH of the ammonia water is 9.

[0022] Preferably, in the step of preparing the graphene oxide dispersion, the ultrasonic treatment conditions include: ultrasonic treatment at 200-400W for 10-30 minutes.

[0023] Preferably, in the step of preparing graphene oxide modified microsphere liquid, the mass-to-volume ratio of the reaction product to the polyethylene glycol solution is 1g:(15-30)ml.

[0024] Preferably, in the step of preparing graphene oxide modified microsphere liquid, the drying method can be a conventional method known to those skilled in the art, such as vacuum drying at 40-60°C for 1-3 hours.

[0025] In a preferred embodiment, the early strength agent is lithium carbonate.

[0026] In a preferred embodiment, the water-reducing agent is a powdered polycarboxylate series high-efficiency water-reducing agent with a water reduction rate of not less than 28%.

[0027] In a preferred embodiment, the retarder is boric acid and / or tartaric acid.

[0028] In a preferred embodiment, the expanding agent is a plastic expanding agent.

[0029] In a preferred embodiment, the defoamer is a powdered silicone defoamer.

[0030] In a preferred embodiment, the early-strength bearing grout has a bleeding rate of 0%, an initial flowability of 360-370 mm, a 30-minute flowability of 330-350 mm, a 2-hour flexural strength of 5.2-5.8 MPa, a 2-hour compressive strength of 28.8-33.2 MPa, a 24-hour flexural strength of 11.8-12.5 MPa, a 24-hour compressive strength of 56.6-66.4 MPa, and a 28-day flexural strength of 13.8- The compressive strength at 28 days is 78.6-89.2 MPa, the ratio of 56-day flexural strength to 28-day flexural strength is 1.10-1.13, the ratio of 56-day compressive strength to 28-day compressive strength is 1.10-1.15, the elastic modulus at 28 days is 38.8-41.6 GPa, the vertical expansion rate at 3 hours is 0.5-0.6%, the difference between the vertical expansion rates at 24 hours and 3 hours is 0.03%, and the free expansion rate at 28 days is 0.05-0.07%.

[0031] Another object of the present invention is to provide a method for preparing any of the above-mentioned shrinkage crack-resistant, high-flowability, early-strength bearing grouting materials, comprising the following steps:

[0032] Accurately weigh the components of the anti-shrinkage cracking high fluidity early strength bearing grout according to the weight fraction, and mix them evenly;

[0033] After mixing the obtained powder with water at a mass ratio of 100:(13-15), stir evenly to obtain a high-flowability, early-strength bearing grout with anti-shrinkage and cracking properties.

[0034] In a preferred embodiment, the mixing method of the mixed powder and water is as follows: first, mix at low speed for 100-140s, then mix at high speed for 40-80s, and finally mix at low speed for 40-80s.

[0035] Preferably, the mixing device is a JJ-5 planetary cement mortar mixer with a rotation speed of 140±5 r / min at low speed and 285±10 r / min at high speed, and a revolution speed of 62±5 r / min at low speed and 125±10 r / min at high speed.

[0036] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0037] 1. The quaternary cement clinker designed in this invention is a low-carbon cement with a firing temperature 100-150℃ lower than that of ordinary silicate cement. It possesses the characteristics of both ordinary silicate cement and sulfoaluminate cement. The early-strength bearing grout prepared using this cement not only has good early strength, but also, due to the calcium sulfoaluminate... The hydration product aluminum hydroxide (AH3) can effectively activate calcium sulfosilicate. The hydration reaction of calcium sulfosilicate makes its hydration activity significantly higher than that of dicalcium silicate (C2S). In the later stages of hydration, with the increase of calcium sulfosilicate... With continuous hydration, the strength of the early-hardening bearing grouting continues to increase, with good volume stability and no shrinkage, which can effectively prevent shrinkage cracking and thus effectively improve the engineering quality after the early-strength bearing grouting construction.

[0038] 2. To address the problem of poor dispersibility of graphene oxide in cement-based materials in existing technologies, this invention designs a specific modification process. Modified fly ash microspheres are mixed with graphene oxide, and then subjected to an N-hydroxysuccinimide catalytic reaction. This allows the -NH2 groups on the surface of the microspheres to form amide bonds with the -COOH groups of the graphene oxide, thereby uniformly loading the graphene material onto the surface of the microsphere matrix. This not only effectively improves the dispersibility of graphene oxide, but also provides numerous nucleation sites for the modified microspheres to accelerate the hydration reaction. Their oxygen-containing functional groups (such as carboxyl and hydroxyl groups) can adsorb calcium ions, guiding the formation of a more regular crystal structure (such as flower-like crystals) in hydrated calcium silicate (CSH) gel, effectively filling pores and bridging microcracks. Although microsphere treatment accelerates the early hydration exothermic rate, graphene oxide effectively optimizes the exothermic pathway, reduces local heat accumulation, and lowers the temperature gradient. In addition, the spherical structure of the modified microspheres can significantly improve the fluidity of the grout, and the grout can reach its maximum initial expansion within 10-15 seconds, which is beneficial for the on-site construction of early-strength bearing grout.

[0039] 3. This invention, through formula design, prepares a high-performance, shrinkage-cracking, high-flowability, early-strength bearing grout with excellent performance. It simultaneously possesses advantages such as high early strength, micro-expansion, shrinkage-cracking resistance, high flowability, long working time, and continuous strength growth in later stages. Compared to traditional early-strength bearing grouts with a 2-hour compressive strength of 20-30 MPa, the early-strength bearing grout prepared by this invention can reach a 2-hour compressive strength of 35-40 MPa, demonstrating excellent early strength. Traditional early-strength bearing grouts typically require 15-20 seconds to reach maximum initial flowability, while the early-strength bearing grout of this invention can reach maximum initial flowability within 10-15 seconds, exhibiting excellent construction performance. Traditional early-strength bearing grouts have a 56-day / 28-day compressive and flexural strength of 1-1.05, while the early-strength bearing grout of this invention has a 56-day / 28-day compressive and flexural strength of 1.10-1.15, with continuous strength growth in later stages, fundamentally solving the shrinkage-cracking problem and possessing outstanding market competitiveness. Detailed Implementation

[0040] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to specific embodiments. However, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0041] Unless otherwise specified, the technical means used in this invention are conventional means well known to those skilled in the art. All raw materials, reagents, instruments, and equipment used in this invention can be purchased commercially or prepared using existing methods. Unless otherwise specified, all reagents used in this invention are of analytical grade. In this invention, the quaternary cement clinker used is a cement clinker product independently developed by our company, specifically patented under CN 114538803 A. The quaternary cement clinker used in the examples was prepared by the method in Example 2 of the patent. In the examples of this invention, the polycarboxylate superplasticizer used is model ZJ-PC8800, purchased from Jiangsu Zhaojia Building Materials Technology Co., Ltd. The plastic expansion agent used is model TC-EA100, purchased from Zhenjiang Tongchuang New Materials Technology Co., Ltd. The defoamer used is model B-328F, purchased from Japan's Adico.

[0042] In this invention, the weight parts can be weight units known in the art such as μg, mg, g, kg, or multiples thereof, such as 1 / 10, 1 / 100, 10 times, 100 times, etc.

[0043] Example 1

[0044] The preparation of graphene oxide modified microspheres specifically includes the following steps:

[0045] S1 Preparation of Modified Fly Ash Microspheres:

[0046] Fly ash microspheres were mixed with a 5% hydrochloric acid solution, shaken at room temperature for 30 minutes, washed with water until neutral, and vacuum dried at 60°C for 2 hours to remove surface impurities, thus obtaining pretreated fly ash microspheres; wherein the mass-to-volume ratio of fly ash microspheres to hydrochloric acid solution was 1 g: 20 ml.

[0047] The pretreated fly ash microspheres were dispersed in a 2% (w / w) γ-aminopropyltriethoxysilane anhydrous ethanol solution and reacted in a 60°C water bath for 4 hours. After washing three times with anhydrous ethanol, modified fly ash microspheres were obtained. The mass-to-volume ratio of the pretreated fly ash microspheres to the γ-aminopropyltriethoxysilane anhydrous ethanol solution was 1 g: 15 ml.

[0048] S2 Preparation of graphene oxide dispersion: Graphene oxide was dispersed in ammonia water at pH=9 and ultrasonically treated with 300W power for 20min to obtain a uniform brownish-brown graphene oxide dispersion; wherein the mass-to-volume ratio of graphene oxide to ammonia water was 0.5mg / ml.

[0049] Preparation of graphene oxide modified microspheres (S3): The prepared modified fly ash microspheres and graphene oxide dispersion were mixed evenly at a mass-to-volume ratio of 1g:25ml. An equal mass of N-hydroxysuccinimide was added to the graphene oxide dispersion. The mixture was stirred and reacted in a water bath at 60℃ for 4 hours. After filtration, the reaction product was collected and immersed in a 10% (mass-to-volume) polyethylene glycol solution (the mass-to-volume ratio of the reaction product to the polyethylene glycol solution was 1g:25ml). The mixture was then reacted in a water bath at 80℃ for 2 hours. The resulting product was dried to obtain the graphene oxide modified microspheres.

[0050] Example 2

[0051] The preparation of a shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grout specifically includes:

[0052] Formula design: 400g quaternary cement clinker, 570g quartz sand, 30g graphene oxide modified microspheres prepared in Example 1, 0.2g lithium carbonate, 2.8g polycarboxylate superplasticizer, 2g boric acid, 1g tartaric acid, 0.3g plastic expansion agent, and 0.6g defoamer. The quartz sand is obtained by blending quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh, and 40-140 mesh in a mass ratio of 3:5:2.

[0053] Preparation method:

[0054] 1. Accurately weigh all raw materials according to the formula design, stir evenly, and obtain a fully mixed powder;

[0055] 2. Add 140g of water to the powder and mix it in a planetary mixer in the following order: low speed for 120s, high speed for 60s, and low speed for 60s (rotation speed is low speed 140r / min, high speed 285r / min, revolution speed is low speed 62r / min, and high speed 125r / min). This will prepare a shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grout.

[0056] The early-strength bearing grout prepared according to JT / T 1130-2017 "Grouting Materials for Bridge Bearings" has the following properties: bleeding rate of 0%, initial flowability of 370 mm, flowability of 335 mm at 30 min, flexural strength of 5.2 MPa at 2 h, compressive strength of 28.8 MPa at 2 h, flexural strength of 11.8 MPa at 24 h, compressive strength of 56.6 MPa at 24 h, flexural strength of 13.8 MPa at 28 d, compressive strength of 78.6 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d, compressive strength / 28 d ratio of 1.10, elastic modulus of 38 d, vertical expansion rate of 0.5% at 3 h, difference between vertical expansion rates at 24 h and 3 h of 0.03%, and free expansion rate of 0.05% at 28 d.

[0057] Example 3

[0058] A shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grout was prepared, differing from Example 2 only in that:

[0059] Formula design: 450g quaternary cement clinker, 520g quartz sand, 30g graphene oxide modified microspheres prepared in Example 1, 0.2g lithium carbonate, 3.0g polycarboxylate superplasticizer, 2.2g boric acid, 1.2g tartaric acid, 0.3g plasticizing agent, and 0.8g defoamer. The quartz sand is obtained by blending quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh, and 40-140 mesh in a mass ratio of 3:5:2.

[0060] The remaining methods and steps are completely consistent with those in Example 2.

[0061] The early-strength bearing grout prepared according to JT / T 1130-2017 "Grouting Materials for Bridge Bearings" has the following properties: bleeding rate of 0%, initial flowability of 360 mm, flowability of 330 mm at 30 min, flexural strength of 5.5 MPa at 2 h, compressive strength of 30.3 MPa at 2 h, flexural strength of 12.0 MPa at 24 h, compressive strength of 60.8 MPa at 24 h, flexural strength of 14.3 MPa at 28 d, compressive strength of 82.5 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d is 1.13, compressive strength / 28 d ratio of 56 d to 28 d is 1.12, elastic modulus of 40.2 GPa at 28 d, vertical expansion rate of 0.6% at 3 h, difference between vertical expansion rates at 24 h and 3 h is 0.03%, and free expansion rate of 0.07% at 28 d.

[0062] Example 4

[0063] A shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grout was prepared, differing from Example 2 only in that:

[0064] Formula design: 450g quaternary cement clinker, 500g quartz sand, 50g graphene oxide modified microspheres prepared in Example 1, 0.2g lithium carbonate, 3.0g polycarboxylate superplasticizer, 2.2g boric acid, 1.2g tartaric acid, 0.3g plasticizing agent, and 0.8g defoamer. The quartz sand is obtained by blending quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh, and 40-140 mesh in a mass ratio of 3:5:2.

[0065] The remaining methods and steps are completely consistent with those in Example 2.

[0066] The early-strength bearing grout prepared according to JT / T 1130-2017 "Grouting Materials for Bridge Bearings" has the following characteristics: bleeding rate of 0%, initial flowability of 370 mm, flowability of 350 mm at 30 min, flexural strength of 5.8 MPa at 2 h, compressive strength of 33.2 MPa at 2 h, flexural strength of 12.5 MPa at 24 h, compressive strength of 66.4 MPa at 24 h, flexural strength of 14.6 MPa at 28 d, compressive strength of 89.2 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d is 1.13, compressive strength / 28 d ratio of 56 d to 28 d is 1.15, elastic modulus of 41.6 GPa at 28 d, vertical expansion rate of 0.6% at 3 h, difference between vertical expansion rates at 24 h and 3 h is 0.03%, and free expansion rate of 0.07% at 28 d.

[0067] Comparative Example 1

[0068] The preparation of an early-strength bearing grout specifically includes:

[0069] Formula design: 450g sulfoaluminate cement, 500g quartz sand, 50g fly ash microsphere raw material used in step S1 of Example 1, 0.2g lithium carbonate, 3.0g polycarboxylate superplasticizer, 2.2g boric acid, 1.2g tartaric acid, 0.3g plastic expansion agent, and 0.8g defoamer. The quartz sand is obtained by blending quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh, and 40-140 mesh in a mass ratio of 3:5:2.

[0070] The preparation method is completely consistent with that in Example 4.

[0071] The early-strength bearing grout prepared according to JT / T1130-2017 "Grouting Materials for Bridge Bearings" has the following properties: bleeding rate of 0%, initial flowability of 330 mm, flowability of 290 mm at 30 min, flexural strength of 5.2 MPa at 2 h, compressive strength of 25.5 MPa at 2 h, flexural strength of 12 MPa at 24 h, compressive strength of 54.2 MPa at 24 h, flexural strength of 13.5 MPa at 28 d, compressive strength of 75.8 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d, compressive strength / 28 d ratio of 56 d to 28 d, elastic modulus of 39.2 GPa at 28 d, vertical expansion rate of 0.3% at 3 h, difference between vertical expansion rates at 24 h and 3 h of 0.02%, and free expansion rate of 0.03% at 28 d.

[0072] Comparative Example 2

[0073] The preparation of an early-strength bearing grout specifically includes:

[0074] Formula design: 450g quaternary cement clinker, 500g quartz sand, 50g fly ash microsphere raw material used in step S1 of Example 1, 0.2g lithium carbonate, 3.0g polycarboxylate superplasticizer, 2.2g boric acid, 1.2g tartaric acid, 0.3g plastic expansion agent, and 0.8g defoamer. The quartz sand is obtained by blending quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh, and 40-140 mesh in a mass ratio of 3:5:2.

[0075] The preparation method is completely consistent with that in Example 4.

[0076] The early-strength bearing grout prepared according to JT / T1130-2017 "Grouting Materials for Bridge Bearings" has the following properties: bleeding rate of 0%, initial flowability of 340 mm, flowability of 320 mm at 30 min, flexural strength of 5.2 MPa at 2 h, compressive strength of 28.9 MPa at 2 h, flexural strength of 12.2 MPa at 24 h, compressive strength of 58.9 MPa at 24 h, flexural strength of 14 MPa at 28 d, compressive strength of 80.9 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d is 1.09, compressive strength / 28 d ratio of 56 d to 28 d is 1.08, elastic modulus of 40.5 GPa at 28 d, vertical expansion rate of 0.5% at 3 h, difference between vertical expansion rates at 24 h and 3 h is 0.03%, and free expansion rate of 0.06% at 28 d.

[0077] Comparative Example 3

[0078] The preparation of an early-strength bearing grout specifically includes:

[0079] Formula design: 450g sulfoaluminate cement, 500g quartz sand, 50g graphene oxide modified microspheres prepared in Example 1, 0.2g lithium carbonate, 3.0g polycarboxylate superplasticizer, 2.2g boric acid, 1.2g tartaric acid, 0.3g plasticizing agent, and 0.8g defoamer. The quartz sand is obtained by blending quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh, and 40-140 mesh in a mass ratio of 3:5:2.

[0080] The preparation method is completely consistent with that in Example 4.

[0081] The early-strength bearing grout prepared according to JT / T1130-2017 "Grouting Materials for Bridge Bearings" has the following properties: bleeding rate of 0%, initial flowability of 360 mm, flowability of 330 mm at 30 min, flexural strength of 5.5 MPa at 2 h, compressive strength of 27.8 MPa at 2 h, flexural strength of 12.3 MPa at 24 h, compressive strength of 57.3 MPa at 24 h, flexural strength of 14.1 MPa at 28 d, compressive strength of 77.6 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d is 1.06, compressive strength / 28 d ratio of 56 d to 28 d is 1.05, elastic modulus of 40.3 GPa at 28 d, vertical expansion rate of 0.5% at 3 h, difference between vertical expansion rates at 24 h and 3 h is 0.03%, and free expansion rate of 0.06% at 28 d.

[0082] Comparative Example 4

[0083] Compared with Example 4, the only difference is that the preparation method of the graphene oxide modified microspheres is different (N-hydroxysuccinimide of the same mass as the graphene oxide dispersion was not added in step S3).

[0084] The remaining methods and steps are completely consistent with those in Example 4.

[0085] The comparative example of preparing graphene oxide modified microspheres specifically includes the following steps:

[0086] S1 Preparation of Modified Fly Ash Microspheres:

[0087] Fly ash microspheres were mixed with a 5% hydrochloric acid solution, shaken at room temperature for 30 minutes, washed with water until neutral, and vacuum dried at 60°C for 2 hours to remove surface impurities, thus obtaining pretreated fly ash microspheres; wherein the mass-to-volume ratio of fly ash microspheres to hydrochloric acid solution was 1 g: 20 ml.

[0088] The pretreated fly ash microspheres were dispersed in a 2% (w / w) γ-aminopropyltriethoxysilane anhydrous ethanol solution and reacted in a 60°C water bath for 4 hours. After washing three times with anhydrous ethanol, modified fly ash microspheres were obtained. The mass-to-volume ratio of the pretreated fly ash microspheres to the γ-aminopropyltriethoxysilane anhydrous ethanol solution was 1 g: 15 ml.

[0089] S2 Preparation of graphene oxide dispersion: Graphene oxide was dispersed in ammonia water at pH=9 and ultrasonically treated with 300W power for 20min to obtain a uniform brownish-brown graphene oxide dispersion; wherein the mass-to-volume ratio of graphene oxide to ammonia water was 0.5mg / ml.

[0090] Preparation of graphene oxide modified microspheres (S3): The prepared modified fly ash microspheres and graphene oxide dispersion were mixed evenly at a mass-to-volume ratio of 1g:25ml. The mixture was stirred and reacted in a water bath at 60℃ for 4 hours. After filtration, the reaction product was collected and immersed in a 10% polyethylene glycol solution (mass-to-volume ratio of reaction product to polyethylene glycol solution was 1g:25ml). The mixture was then reacted in a water bath at 80℃ for 2 hours. The resulting product was dried to obtain graphene oxide modified microspheres.

[0091] The early-strength bearing grout prepared according to JT / T1130-2017 "Grouting Materials for Bridge Bearings" has the following properties: bleeding rate of 0%, initial flowability of 340 mm, flowability of 330 mm at 30 min, flexural strength of 5.3 MPa at 2 h, compressive strength of 29.5 MPa at 2 h, flexural strength of 12.2 MPa at 24 h, compressive strength of 60.2 MPa at 24 h, flexural strength of 14 MPa at 28 d, compressive strength of 85.6 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d is 1.1, compressive strength / 28 d ratio of 56 d to 28 d is 1.11, elastic modulus of 40.6 GPa at 28 d, vertical expansion rate of 0.6% at 3 h, difference between vertical expansion rates at 24 h and 3 h is 0.03%, and free expansion rate of 0.07% at 28 d.

[0092] Comparative Example 5

[0093] Compared with Example 4, the only difference is that the preparation method of graphene oxide modified microspheres is different (the mass-to-volume ratio of graphene oxide and ammonia in step S2 is 0.25 mg / ml).

[0094] The remaining methods and steps are completely consistent with those in Example 4.

[0095] The comparative example of preparing graphene oxide modified microspheres specifically includes the following steps:

[0096] S1 Preparation of Modified Fly Ash Microspheres:

[0097] Fly ash microspheres were mixed with a 5% hydrochloric acid solution, shaken at room temperature for 30 minutes, washed with water until neutral, and vacuum dried at 60°C for 2 hours to remove surface impurities, thus obtaining pretreated fly ash microspheres; wherein the mass-to-volume ratio of fly ash microspheres to hydrochloric acid solution was 1 g: 20 ml.

[0098] The pretreated fly ash microspheres were dispersed in a 2% (w / w) γ-aminopropyltriethoxysilane anhydrous ethanol solution and reacted in a 60°C water bath for 4 hours. After washing three times with anhydrous ethanol, modified fly ash microspheres were obtained. The mass-to-volume ratio of the pretreated fly ash microspheres to the γ-aminopropyltriethoxysilane anhydrous ethanol solution was 1 g: 15 ml.

[0099] S2 Preparation of graphene oxide dispersion: Graphene oxide was dispersed in ammonia water at pH=9 and ultrasonically treated with 300W power for 20min to obtain a uniform brownish-brown graphene oxide dispersion; wherein the mass-to-volume ratio of graphene oxide to ammonia water was 0.25mg / ml.

[0100] Preparation of graphene oxide modified microspheres (S3): The prepared modified fly ash microspheres and graphene oxide dispersion were mixed evenly at a mass-to-volume ratio of 1g:25ml. An equal mass of N-hydroxysuccinimide was added to the graphene oxide dispersion. The mixture was stirred and reacted in a water bath at 60℃ for 4 hours. After filtration, the reaction product was collected and immersed in a 10% (mass-to-volume) polyethylene glycol solution (the mass-to-volume ratio of the reaction product to the polyethylene glycol solution was 1g:25ml). The mixture was then reacted in a water bath at 80℃ for 2 hours. The resulting product was dried to obtain the graphene oxide modified microspheres.

[0101] The early-strength bearing grout prepared according to JT / T1130-2017 "Grouting Materials for Bridge Bearings" has the following properties: bleeding rate of 0%, initial flowability of 350 mm, flowability of 330 mm at 30 min, flexural strength of 5.5 MPa at 2 h, compressive strength of 30 MPa at 2 h, flexural strength of 12.4 MPa at 24 h, compressive strength of 63.1 MPa at 24 h, flexural strength of 14.3 MPa at 28 d, compressive strength of 88.6 MPa at 28 d, flexural strength / 28 d ratio of 56 d to 28 d is 1.11, compressive strength / 28 d ratio of 56 d to 28 d is 1.13, elastic modulus of 40.9 GPa at 28 d, vertical expansion rate of 0.6% at 3 h, difference between vertical expansion rates at 24 h and 3 h is 0.03%, and free expansion rate of 0.07% at 28 d.

[0102] Comparative Example 6

[0103] Compared with Example 4, the only difference is that the quartz sand in this comparative example is obtained by compounding quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh and 40-140 mesh in a mass ratio of 5:3:2.

[0104] The remaining methods and steps are completely consistent with those in Example 4.

[0105] The early-strength bearing grout prepared according to JT / T1130-2017 "Grouting Materials for Bridge Bearings" has the following characteristics: 0% bleeding rate, initial flowability of 335 mm, 290 mm flowability at 30 min, 2-hour flexural strength of 5 MPa, 2-hour compressive strength of 26.8 MPa, 24-hour flexural strength of 11.8 MPa, 24-hour compressive strength of 55.2 MPa, 28-day flexural strength of 13.3 MPa, 28-day compressive strength of 77.2 MPa, 56-day flexural strength / 28-day flexural strength ratio of 1.09, 56-day compressive strength / 28-day compressive strength ratio of 1.08, 28-day elastic modulus of 40.2 GPa, 3-hour vertical expansion rate of 0.6%, difference between 24-hour and 3-hour vertical expansion rates of 0.03%, and 28-day free expansion rate of 0.06%.

[0106] The specific test data for Examples 2-4 and Comparative Examples 1-6 are shown in Tables 1 and 2.

[0107] Table 1

[0108]

[0109] Table 2

[0110]

[0111] In summary, it can be seen that the graphene oxide modified microspheres prepared by the present invention through a specific method, and the significant synergistic effect of the modified microspheres with quaternary cement clinker and specific graded quartz sand, not only effectively solve the shrinkage cracking and strength reduction problems that occur in the later use of traditional early-strength bearing grouting materials, but also alleviate the adverse effects of the concentrated early hydration heat release phenomenon on material safety, while comprehensively improving the workability and performance stability of the product, providing a reliable guarantee for achieving engineering safety and quality.

[0112] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grout, characterized in that, By weight, it includes the following components: 40-50 parts of quaternary cement clinker, 45-55 parts of quartz sand, 3-5 parts of graphene oxide modified microspheres, 0.01-0.03 parts of early strength agent, 0.2-0.4 parts of water-reducing agent, 0.3-0.5 parts of retarder, 0.03-0.05 parts of expansion agent and 0.05-0.08 parts of defoamer.

2. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 1, characterized in that, The quartz sand is obtained by mixing quartz sand particles with particle sizes of 10-20 mesh, 20-40 mesh and 40-140 mesh in a mass ratio of 3:5:

2.

3. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 1, characterized in that, The graphene oxide modified microspheres are prepared by the following steps: Preparation of modified fly ash microspheres: The pretreated fly ash microspheres were dispersed in anhydrous ethanol solution of γ-aminopropyltriethoxysilane and reacted in a water bath to obtain modified fly ash microspheres. Preparation of graphene oxide dispersion: Graphene oxide was dispersed in ammonia water and ultrasonically treated to obtain graphene oxide dispersion. Preparation of graphene oxide modified microspheres: The prepared modified fly ash microspheres and graphene oxide dispersion were mixed evenly at a mass-to-volume ratio of 1g:(20-30)ml. N-hydroxysuccinimide of the same mass as the graphene oxide dispersion was added. The mixture was stirred and reacted in a water bath at 55-65℃ for 3-5 hours. After filtration, the reaction product was collected and immersed in a polyethylene glycol solution with a mass fraction of 8-12%. The mixture was then reacted in a water bath at 70-90℃ for 1-3 hours. The resulting product was dried to obtain graphene oxide modified microspheres.

4. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 3, characterized in that, In the step of preparing modified fly ash microspheres, the pretreatment method of the fly ash microspheres specifically includes: mixing fly ash microspheres with a hydrochloric acid solution with a mass fraction of 2-10%, shaking at room temperature for 10-30 minutes, washing, and drying to obtain the product.

5. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 3, characterized in that, In the step of preparing modified fly ash microspheres, the mass-to-volume ratio of the pretreated fly ash microspheres and the γ-aminopropyltriethoxysilane anhydrous ethanol solution is 1 g: (10-20) ml. The mass fraction of the γ-aminopropyltriethoxysilane anhydrous ethanol solution is 1-3%.

6. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 3, characterized in that, In the step of preparing the graphene oxide dispersion, the mass-to-volume ratio of the graphene oxide and ammonia is (0.2-0.8) mg / ml; The pH of the ammonia solution is 8-10.

7. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 3, characterized in that, In the step of preparing graphene oxide modified microsphere liquid, the mass-to-volume ratio of the reaction product to the polyethylene glycol solution is 1 g: (15-30) ml.

8. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 1, characterized in that, The early strength agent is lithium carbonate; the water-reducing agent is a powdered polycarboxylate series high-efficiency water-reducing agent with a water reduction rate of not less than 28%; the retarder is boric acid and / or tartaric acid; the expanding agent is a plastic expanding agent; and the defoamer is a powdered organosilicon defoamer.

9. The shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material as described in claim 1, characterized in that, The aforementioned early-strength bearing grout has a bleeding rate of 0%, an initial flowability of 360-370 mm, a 30-minute flowability of 330-350 mm, a 2-hour flexural strength of 5.2-5.8 MPa, a 2-hour compressive strength of 28.8-33.2 MPa, a 24-hour flexural strength of 11.8-12.5 MPa, a 24-hour compressive strength of 56.6-66.4 MPa, and a 28-day flexural strength of 13.8-14.6 MPa. a. 28-day compressive strength is 78.6-89.2 MPa; 56-day flexural strength / 28-day flexural strength ratio is 1.10-1.13; 56-day compressive strength / 28-day compressive strength ratio is 1.10-1.15; 28-day elastic modulus is 38.8-41.6 GPa; 3-hour vertical expansion rate is 0.5-0.6%; the difference between 24-hour and 3-hour vertical expansion rates is 0.03%; 28-day free expansion rate is 0.05-0.07%.

10. The preparation method of the shrinkage-resistant, crack-resistant, high-flowability, early-strength bearing grouting material according to any one of claims 1-9, characterized in that, Includes the following steps: Accurately weigh the components of the anti-shrinkage cracking high fluidity early strength bearing grouting material according to any one of claims 1-9 by weight fraction, and mix them evenly; After mixing the obtained powder with water at a mass ratio of 100:(13-15), stir evenly to obtain a high-flowability, early-strength bearing grout with anti-shrinkage and cracking properties.

Citation Information

Patent Citations

  • Low-carbon high-strength micro-expansive cement clinker as well as preparation method and application thereof

    CN114538803A